PERBANDINGAN EFEKTIVITAS CEFOTAXIME DAN CEFTRIAXONE PADA PASIEN RAWAT INAP PEDIATRI DENGAN PNEUMONIA - Rosnarita, Intan Adevia; Akhyasin, Akhtyasin; Dewi, Sintia Kusuma (IJF (Indonesia Jurnal Farmasi), 2024)
The prevalence of pneumonia for pediatrics in Indonesia is quite high. This condition is a concern for clinicians, especially pharmacists in handling the treatment of pneumonia in pediatrics. Treatment of pneumonia for pediatrics needs antibiotic therapy such as cefotaxime and ceftriaxone. This study aims to compare the effectiveness of the use of antibiotics cefotaxime and ceftriaxone in pediatric pneumonia patients at the inpatient installation of RSI Sunan Kudus Period February-April 2021. This study is a non-experimental research study with an observational analytic character, with purposive sampling, statistical analysis was carried out To compare the effectiveness of using cefotaxime and ceftriaxone based on duration of use and clinical symptoms, SPSS was performed using Paired T-Test. Based on the average duration of use for antibiotics cefotaxime 5 days and ceftriaxone 4.41 days. There was no difference in the average use of cefotaxime and ceftriaxone based on clinical symptoms such as cough, retractions, fever, shortness of breath and sore throat. The results of statistical analysis showed that ceftriaxone was more effective than cefotaxime in pediatric pneumonia, while there was no significant difference between ceftriaxone and cefotaxime (α) 0.05. The use of ceftriaxone is more effective in treating pediatric pneumonia than cefotaxime.